2023
DOI: 10.5194/egusphere-2022-1518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New insights into the Weddell Sea ecosystem applying a quantitative network approach

Abstract: Abstract. Network approaches can shed light on the structure and stability of complex marine communities. In recent years, such approaches have been successfully applied to study polar ecosystems, improving our knowledge on how they might respond to ongoing environmental changes. The Weddell Sea is one of the most studied marine ecosystems outside the Antarctic Peninsula in the Southern Ocean. Yet, few studies consider the known complexity of the Weddell Sea food web, which in its current form comprises 490 sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
1
0
1
Order By: Relevance
“…Our findings show some discrepancies with those of Marina et al (2024), who applied the same method to calculate interaction strength for the Weddell Sea (Antarctica) food web, without incorporating empirical density/biomass values. They found a positive relationship between species interaction strength, trophic level, and degree.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Our findings show some discrepancies with those of Marina et al (2024), who applied the same method to calculate interaction strength for the Weddell Sea (Antarctica) food web, without incorporating empirical density/biomass values. They found a positive relationship between species interaction strength, trophic level, and degree.…”
Section: Discussioncontrasting
confidence: 98%
“…The estimation of the species interaction strength for the Potter Cove food web allowed us a better understanding of species' role in food web stability. We found that the distribution of interaction strength was skewed toward a few strong and many weak links, as observed in extensive theoretical and empirical studies (Drossel et al, 2004;Kortsch et al, 2021;Marina et al, 2024; J. T. Wootton & Emmerson, 2005). This asymmetrical pattern has been proposed to promote ecosystem persistence and stability (Bascompte et al, 2005;Drossel et al, 2004;Emmerson & Yearsley, 2004;McCann et al, 1998).…”
Section: Discussionsupporting
confidence: 72%